41st Annual David W. Smith workshop on malformations and morphogenesis: Abstracts of the 2020 annual meeting. Issue 4 (12th January 2021) - Gripp, Karen W.; Jones, Kenneth Lyons; Wenger, Tara L.; ,; Adam, Margaret P.
Abstract: The 41st Annual David W. Smith Workshop on Malformation and Morphogenesis was scheduled to take place in Skamania, Washington, on September 11–16, 2020. Due to the COVID‐19 pandemic and the associated recommendations to avoid travel and congregation in large groups, this meeting took place differently from its original plan. Rather than bringing trainees, clinicians and researchers with an interest in congenital malformations and their underlying morphogenesis together for several days in a workshop with submitted presentations and research lectures, this meeting took place virtually. A 1 day online meeting was organized in order to allow trainees to present their work. This Conference Report includes the highest scoring abstracts submitted by trainees and presented at the 2020 virtual David W. Smith Workshop.